Patient Dose Comparison for Intraoperative Imaging Devices Used in Orthopaedic Lumbar Spinal Surgery. (July 2018) - Moore, Bria; Womack, K. Roland; Nguyen, Giao; Foster, Norah; Richardson, William; Yoshizumi, Terry
Abstract : Background: The aim of this study was to determine the amount of radiation exposure from intraoperative imaging during two-level and four-level lumbar fusions. Methods: Five imaging systems were studied: multidetector CT (MDCT) scanner (CT A); two mobile CT units (CT B and CT C); a C-arm (D); and fluoroscopy (E). Metal oxide semiconductor field effect transistor dosimeters measured doses at 25 organ locations using an anthropomorphic phantom. A fat-equivalent phantom was used to simulate an obese body mass index (BMI). Results: The effective dose (ED) for C-arm D was estimated using commercial software. The ED for others was computed from the measured mean organ doses. EDs for a normal BMI patient, receiving a four-level fusion, are as follows: CT A (12.00 ± 0.30 mSv), CT B (5.90 ± 0.25 mSv), CT C (2.35 ± 0.44 mSv), C-arm D (0.44 mSv), and fluoroscopy E (0.30 ± 0.3 mSv). The rankings are consistent across all three BMI values except CT C and fluoroscopy E, which peaked in the overweight size because of system limitations. The other machines' ED trended with patient BMI. Conclusion: The dose reduction protocols were confirmed according to the manufacturer's specifications. The results of this study emphasize the need for the appropriate selection of the imaging system, especially because the type of device could have a substantial effect on patient radiation risk.